Has the Comprehensive Assessment made the European financial system more resilient? - Silvia Calò; Wildmer Daniel Gregori; Marco Petracco Giudici; Michela Rancan (European Commission, 2021)
What has been the impact of the Comprehensive Assessment (CA) carried out by the ECB on banks' resilience? Implementing a difference-indifference approach, we analyse a non-risk based measure defined as the ratio of Tier 1 capital over total assets of European banks' balance sheets during the years 2007-2018. This wide time span, compared to previous literature, allows a better analysis of CA's medium-term effects. We find that banks under the CA have a higher ratio, suggesting that the CA has contributed to foster banks' resilience. Importantly, this seems to have been achieved by banks increasing their capitalization level without shrinking their assets. In addition, this impact appears to be driven by banks located in countries where the regulatory environment and property rights are relatively less strong.
Keywords: G21; G28; 330; Comprehensive assessment; European banks; Financial stability; Regulation